Dynamic Process of Secondary Pulmonary Infection in Mice With Intracerebral Hemorrhage - Hanyu Zhang (Frontiers Media S.A., 2021)
Stroke is a common central nervous system disease in clinical practice. Stroke patients often have infectious complications, such as pneumonia and infections of the urinary tract and gastrointestinal tract. Although it has been shown that translocation of the host gut microbiota to the lungs and immune dysfunction plays a vital role in the development of infection after ischemic stroke, the occurrence and mechanism of pulmonary infection at different time points after hemorrhagic cerebral remain unclear. In this study, the changes in the immune system and intestinal barrier function in mice during disease development were investigated at 1 day (M 1 d), 3 days (M 3 d) and 7 days (M 7 d) following hemorrhagic stroke to clarify the mechanism of secondary pulmonary infection. The experimental results revealed that after hemorrhagic stroke, model mice showed increased brain damage from day 1 to 3, followed by a trend of brain recovery from day 3 to 7 . After hemorrhagic stroke, the immune system was disturbed in model mice. Significant immunosuppression of the peripheral immune system was observed in the M 3 d group but improved in the M 7 d group. Staining of lung tissues with hematoxylin and eosin (H&E) and for inflammatory factors revealed considerable disease and immune disorders in the M 7 d group. Stroke seriously impaired intestinal barrier function in mice and significantly changed the small intestine structure. From 1 to 7 d after stroke, intestinal permeability was increased, whereas the levels of markers for intestinal tight junctions, mucus and immunoglobulin A were decreased. Analysis based on 16S rRNA suggested that the microflora in the lung and ileum was significantly altered after stroke. The composition of microflora in lung and ileum tissue was similar in the M 7d group, suggesting that intestinal bacteria had migrated to lung tissue and caused lung infection at this time point after hemorrhagic stroke. In stroke mice, the aggravation of intestinal barrier dysfunction and immune disorders after intracerebral hemorrhage, promoted the migration of enteric bacteria, and increased the risk of pneumonia poststroke. Our findings reveal the dynamic process of infection after hemorrhagic stroke and provide clues for the optimal timing of intervention for secondary pulmonary infection in stroke patients.